The small agricultural credit in Ivory-Coast - Banque Nationale Pour Le Developpeement Agriculture (Ivory-Coast : Banque Nationale Pour Le Developpement Agriculture, 1973)
This work discusses on agricultural products and small planter's credit facilities.
Includes bibliographical references.
mf 23/01/2019
Loans
Keywords: Agricultural credit